Phenotypic and genetic diversity of watermelon (Citrullus lanatus) in East Java, Indonesia - Achmad Amzeri; Kaswan Badami; Pawana Gita; Moh. Alfiyan Syah; Budi Setiadi Daryono (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Amzeri A, Badami K, Pawana G, Alfiyan Syah M, Daryono BS. 2021. Phenotypic and genetic diversity of watermelon (Citrullus lanatus) in East Java, Indonesia. Biodiversitas 22: 5223-5230. The assembly of hybrid watermelon (Citrullus lanatus Thumb.) varieties with superior characters is an effort to meet the needs of watermelon seeds in Indonesia and reduce dependence on imports of watermelon seeds.  The morphological characterization of exploratory watermelon plants is needed to support the assembly of superior varieties because morphological characterization will reveal the characteristics of each watermelon tested.  In addition, the genetic and phenotypic diversity coefficients, heritability, and correlation between characters are needed to support the assembling of the desired variety.  This research aimed to determine morphological diversity, genetic and phenotypic diversity coefficients, heritability, and correlation among characters of watermelon from East Java, Indonesia.  The research used a randomized complete block design with ten genotypes as treatment and three replications,. The observed morphological characters were quantitative and qualitative characters.  The number of characters was 60 characters.  Eight quantitative characters, i.e., flowering date, harvesting date, fruit length, fruit diameter, skin thickness, fruit total soluble solids, number of seeds, and fruit weight were used to calculate the genetic and phenotypic diversity coefficient, heritability, and correlation between characters.  Quantitative character data were subjected to analysis of variance, followed with a Duncan Multiple Range Test (p<0.05).  The results showed that (i) Grouping based on morphological characters produces dendrograms with similarity coefficients ranging from 0.58 to 0.86 or there was a morphological diversity of 0.14 to 0.42, (ii) The phenotypic diversity coefficient (PDC) was greater than the genotypic diversity coefficient (PDC) in all observed quantitative characters, (iii) The broad sense Heritability values ?? of the tested watermelon genotypes ranged from 0.33 to 0.99, (iv) Fruit weight was significantly and positively correlated with fruit diameter, skin thickness, and number of seeds, (v) G1, G2, and G6 were the genotypes that can be used as parents to assemble superior watermelon varieties.